Diseño de un sistema estructural electromecánico para un seguidor solar didáctico de paneles fotovoltaicos (2020)
The main objective of this undergraduate project is to design an electromechanical structural system for a photovoltaic panel solar tracker, governed by a series of resources and basic mechanical methods.